Governor Demands Coast Sub Building - Unknown (Unknown)
Gov. Edmund G. (Pat) Brown yesterday pledged his full support in bringing construction of nuclear submarines to private shipbuilding yards in California but at the same time declared this program would in no way interfere with the building program at Mare Island Naval Shipyard.